2011
DOI: 10.1136/sextrans-2011-050209
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of HIV-1 drug resistance in Benin could jeopardise future treatment options

Abstract: Although our results show a low rate of SDMR, this algorithm may underestimate resistance mutations that may impact treatment options in developing countries. Primary resistance rates were similar in CSW and in the GP. Our phylogenetic analysis confirmed the genetic exchange between groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 13 publications
2
16
0
Order By: Relevance
“…Only Nigeria ( n  = 183) and Cameroon ( n  = 31) were represented by a high or relatively high number of sequences. Other western (Benin, Niger, and Togo) and central (Central African Republic, Chad, Equatorial Guinea, and Gabon) African countries with circulation of subtype G at significant levels (≥5% of all HIV-1 infections) [13], [14], [15], [16], [17], [67], [68], [69], [70], [71], [72] were represented by a small number of sequences ( n ≤15) that may not fully reflect the country’s subtype G diversity, or were not represented at all in our study (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only Nigeria ( n  = 183) and Cameroon ( n  = 31) were represented by a high or relatively high number of sequences. Other western (Benin, Niger, and Togo) and central (Central African Republic, Chad, Equatorial Guinea, and Gabon) African countries with circulation of subtype G at significant levels (≥5% of all HIV-1 infections) [13], [14], [15], [16], [17], [67], [68], [69], [70], [71], [72] were represented by a small number of sequences ( n ≤15) that may not fully reflect the country’s subtype G diversity, or were not represented at all in our study (Fig. S2).…”
Section: Discussionmentioning
confidence: 99%
“…Subtype G is the second most prevalent HIV-1 clade in West Africa accounting for nearly 30% of infections in the region [4]. Its prevalence greatly varies within and between countries, comprising 30–50% of HIV-1 infections across different regions from Nigeria [5], [6], [7], [8], [9], [10], [11], [12], 5–15% in Benin, Niger and Togo [13], [14], [15], [16], [17], and ≤4% in other western African countries [14], [18], [19], [20], [21], [22], [23], [24], [25], [26], [27], [28], [29], [30]. Similarly, the occurrence of the CRF06_cpx clade ranges from 40–50% of HIV-1 infections in Burkina Faso [18], [19], [20], to 5–15% in Benin, Ghana, Mali, Niger, Nigeria, Senegal and Togo [5], [6], [7], [8], [9], [10], [11], [12], [13], [14], [15], [16], [17], [21], [22], [23], [24], [28], [29], and <3% in other western African countries [14], [26], [27], [30].…”
Section: Introductionmentioning
confidence: 99%
“…Encouragingly, recent studies have investigated, but not found, increases in ART resistance mutations in SW. 40,41 Several groups have reported significant clustering of HIV subtypes by sex work status, clade differences from other high risk groups, linkage with general population samples, and high proportions of dual, multiple, and recombinant HIV infections. (Table 2) These findings are consistent with the multiple and repeated exposures.…”
Section: Diversity and Communalitymentioning
confidence: 99%
“…1C and D). Because it has been reported that neutralizing antibodies are generally strain specific, being able to neutralize only the patient's own (autologous) virus, 21 we repeated these neutralization assays with viral particles bearing a clade A Env (predominant subtype in Benin) 22 and again we did not detect any significant neutralization in the samples of HIV-1-uninfected CSWs (not shown). We then investigated whether sera and CVL samples of CSWs could eliminate gp120-coated target cells through ADCC.…”
mentioning
confidence: 91%